Copper alloy powder for laminated shaping, copper alloy laminated shaped body, and method for

By containing nickel and silicon in the copper alloy powder, and laminated and molded in the laminated and stacked shape device, combined with aging treatment, the problem of the inability to generate a high-strength copper alloy layered shape in the prior art is solved, and a high-strength copper alloy is realized Manufacturing of laminated shapes.

CN119421752APending Publication Date: 2025-02-11FUKUDA METAL FOIL & POWDER CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280097400.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-06-24
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art cannot effectively generate Cosson alloys containing nickel and silicon, resulting in the inability to manufacture high-strength copper alloy laminated shapes.

Method used

By using a copper alloy powder containing nickel and silicon, and laminated in a laminated shape in a laminated shape device, combined with aging treatment of 450°C or above or below 550°C, a high-strength copper alloy laminated shape is generated.

Benefits of technology

The Cosson alloy containing nickel and silicon is effectively generated, thereby producing a high-strength copper alloy layered shape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119421752A_ABST
    Figure CN119421752A_ABST
Patent Text Reader

Abstract

According to the present invention, it is possible to produce a high-strength copper alloy laminated molded body by efficiently producing a Keson alloy containing nickel and silicon. Provided is a copper alloy powder for laminate molding for molding a laminate molded body by a laminate molding method, the copper alloy powder containing nickel and silicon, the remainder comprising copper and unavoidable impurities, and the value obtained by dividing the nickel content (wt%) by the silicon content (wt%) being 3.3-7.2 (inclusive). Furthermore, provided is a copper alloy laminate molded body obtained by laminate molding using a laminate molding device, the value obtained by dividing the content (wt%) of nickel by the content (wt%) of silicon being 3.3-7.2, the copper alloy laminate molded body containing 1.5-6.0 wt% of nickel and 0.35-1.5 wt% of silicon, the copper alloy laminate molded body being characterized in that the content (wt%) of nickel is less than or equal to 0.5 wt% and the content (wt%) of silicon is less than or equal to 0.5 wt% and the content (wt%) of silicon is less than or equal to 0.5 wt%. The remainder is composed of copper and unavoidable impurities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to copper alloy powder for laminated molding, a copper alloy laminated molding body and a method for producing the copper alloy laminated molding body. Background Art

[0002] In the above-mentioned technical field, Patent Document 1 discloses a copper-based alloy powder for laminated molding containing nickel and silicon elements in copper.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2021-017639 Summary of the invention

[0006] Problems to be solved by the invention

[0007] However, in the technology described in the above document, a Corson alloy containing nickel and silicon is not effectively produced, and therefore a high-strength copper alloy laminated body cannot be produced.

[0008] An object of the present invention is to provide a technology for solving the above-mentioned problems.

[0009] Means for solving problems

[0010] In order to achieve the above-mentioned object, the copper alloy powder for laminated molding according to the present invention is a copper alloy powder for laminated molding used for molding a laminated body by a laminated molding method.

[0011] The copper alloy powder for laminated molding contains nickel and silicon, and the remainder is composed of copper and inevitable impurities.

[0012] The value obtained by dividing the nickel content (weight %) by the silicon content (weight %) is 3.3 or more and 7.2 or less.

[0013] In order to achieve the above-mentioned object, the copper alloy laminated body according to the present invention is a copper alloy laminated body obtained by using the above-mentioned copper alloy powder for laminated forming and performing laminated forming using a laminated forming apparatus.

[0014] The value obtained by dividing the nickel content (weight %) by the silicon content (weight %) is 3.3 or more and 7.2 or less.

[0015] In order to achieve the above-mentioned object, the manufacturing method of the copper alloy stacked body according to the present invention comprises:

[0016] Using the copper alloy powder for stacking molding, a copper alloy stacking body is stacked and molded by a stacking molding device; and

[0017] The copper alloy laminated body is maintained at a temperature of 450°C to 550°C.

[0018] Effects of the Invention

[0019] According to the present invention, a high-strength copper alloy laminated body can be manufactured by efficiently generating a Corson alloy containing nickel and silicon. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] [ Figure 1 ] is a diagram showing the characteristics of the copper alloy laminated bodies of Examples 1 to 6 and Comparative Examples 5 to 12.

[0021] [ Figure 2 ] is a graph showing the changes in characteristics of the copper alloy laminated bodies of Examples 1 to 6 caused by aging treatment.

[0022] [ Figure 3 ] is a diagram showing the characteristics of the copper alloy laminated bodies of Examples 10 to 19.

[0023] [ Figure 4 ] is a graph showing the changes in characteristics of the copper alloy laminated bodies of Examples 10 to 19 caused by aging treatment.

[0024] [ Figure 5 ] is a diagram showing the characteristics of the copper alloy laminated bodies of Examples 1 to 6 and 10 to 19 and Comparative Examples 21 to 34 and Comparative Examples 41 to 54. DETAILED DESCRIPTION

[0025] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the components described in the following embodiments are merely illustrative, and the technical scope of the present invention is not limited thereto.

[0026] [First embodiment]

[0027] In the present embodiment, a copper alloy powder for laminated molding containing nickel and silicon with the remainder being copper and inevitable impurities, and a copper alloy laminated molding body obtained by laminated molding using the copper alloy powder for laminated molding are described.

[0028] <Manufacturing of Copper Alloy Powder for Laminated Molding>

[0029] The method for manufacturing the copper alloy powder for stacking molding of the present embodiment is not particularly limited, and preferably a method in which the powder particles are quenched and solidified from a molten state, such as gas atomization, water atomization, centrifugal atomization, plasma atomization, plasma rotating electrode method, etc. is used. From the perspective of mass production, gas atomization is particularly preferred. The manufactured powder can be classified under prescribed classification conditions using a known classification method to adjust the copper alloy powder for stacking molding to a suitable particle size. As a classification device for implementing the classification, an air flow classifier can be preferably used.

[0030] (Conditions of Metals Contained in Copper Alloy Powder for Laminated Forming of the Present Embodiment)

[0031] In Corson alloys, which are precipitation-strengthened copper alloys, nickel and silicon that are supersaturatedly dissolved in copper as a matrix form a nickel-silicon intermetallic compound through aging treatment and precipitate, thereby improving the strength of the copper alloy.

[0032] In order to obtain a copper alloy laminated body with high mechanical strength, the content of nickel is preferably 1.5% by weight or more. In the case of less than 1.5% by weight, the amount of precipitation becomes insufficient during aging treatment, and the effect of strength improvement cannot be fully obtained. It should be noted that, with respect to the solid solubility limit of Ni2Si, one of the nickel-silicon intermetallic compounds in Corson alloy, it can be said that nickel is about 4.2% by weight and silicon is 1.0% by weight. However, in the case of using a method such as atomization to melt the metal and rapidly solidify it as a powder manufacturing method, the nickel-silicon intermetallic compound above the solid solubility limit can be contained in the copper matrix without precipitation.

[0033] In addition, in the case of a layered molding method using a powder bed fusion method, from the process point of view, melting and rapid solidification based on a laser or electron beam are performed, so that a molded body can be produced without precipitating a nickel-silicon intermetallic compound above the solid solubility limit. However, when the nickel content is greater than 6.0% by weight, although the effect of further improving the mechanical strength can be obtained, it will lead to a significant decrease in electrical conductivity. Therefore, the nickel content is preferably 6.0% by weight or less.

[0034] Silicon is a main element that forms a nickel-silicon intermetallic compound with nickel and precipitates, and contributes to improving the strength of the copper alloy. When its content is less than 0.35 wt%, the amount of precipitation during the aging treatment becomes insufficient, and the effect of improving strength cannot be fully obtained. In addition, if it is more than 1.5 wt%, the conductivity is greatly reduced, and coarse precipitates are generated, which leads to a decrease in strength, so it is preferably within the range of this embodiment.

[0035] Nickel and silicon are the main elements that form nickel-silicon intermetallic compounds and contribute to improving electrical conductivity and strength. However, in order to improve both electrical conductivity and strength, nickel and silicon need to be contained in a ratio effective for forming nickel-silicon intermetallic compounds within their respective content ranges. The ratio is preferably such that the value obtained by dividing the nickel content (weight %) by the silicon content (weight %) is in the range of 3.3 to 7.2. When the ratio is greater than 7.2 and nickel is contained in excess relative to silicon, the excess amount of nickel is dissolved in the copper matrix, and thus the electrical conductivity is greatly reduced. On the other hand, when the ratio is less than 3.3 and silicon is contained in excess relative to nickel, the excess amount of silicon is dissolved in the copper matrix, and thus the electrical conductivity is greatly reduced.

[0036] (Conditions of Physical Properties of Copper Alloy Powder for Laminated Forming of the Present Embodiment)

[0037] The powder used for layered molding is required to be suitable for the various processes of layered molding, such as the supply process from the hopper to the molding table, the process of forming a powder layer evenly spread with a certain thickness, and the process of melting and solidification. Therefore, the following conditions are required. The conditions refer to the flowability of the powder that can be supplied from the supply hopper and form an appropriate powder layer, which is adjusted to a particle size within an appropriate range, an apparent density within an appropriate range, and can be supplied from the supply hopper and can form an appropriate powder layer.

[0038] The 50% particle size of the copper alloy powder for stacking molding is the 50% particle size of the particle size distribution when measured by laser diffraction method, and is preferably included in the range of 3 μm to 200 μm. When the 50% particle size is less than 3 μm, the fluidity of the powder disappears, and the powder layer cannot be formed even in the stacking molding device of the laser powder bed melting method. In addition, when the laser is irradiated on the powder with a 50% particle size less than 3 μm, the powder and the droplets generated by the melting of the powder are scattered, so it is not suitable for stacking molding. When the 50% particle size is greater than 100 μm when stacking molding is performed by laser powder bed melting method, and when the 50% particle size is greater than 200 μm when stacking molding is performed by electron beam powder bed melting method, the surface of the powder layer is rough and a powder layer suitable for molding cannot be formed. In addition, the molten pool generated in the powder layer during electron beam irradiation does not reach the solidification layer directly below, resulting in insufficient melting and solidification, so it is not suitable for stacking molding.

[0039] In the laser powder bed fusion method, the 50% particle size is preferably 3 μm to 100 μm, more preferably 5 μm to 75 μm, and even more preferably 10 μm to 45 μm. In the electron beam powder bed fusion method, the 50% particle size is preferably 10 μm to 200 μm, more preferably 25 μm to 150 μm, and even more preferably 45 μm to 105 μm.

[0040] The copper alloy powder for lamination molding that can be laminated by the lamination molding apparatus needs to have an apparent density (AD: Apparent Density) of 3.0 g / cm when measured by the measurement method of JIS Z2504 in accordance with ISO 3923-1. 3 Above. The apparent density is less than 3.0g / cm 3 In the case of , the powder filling rate of the powder layer filled by brushing is reduced, and an appropriate powder layer cannot be formed. In addition, due to the reduced filling rate of the powder, pores are generated in the shape, and the density of the shape is reduced. In order to obtain a high-density laminated shape, the apparent density of the copper alloy powder for laminated molding is more preferably 3.5 g / cm 3 above.

[0041] In the layered molding method, fluidity is a particularly important powder property. Especially in the powder bed fusion method, it is the most important powder property directly related to the quality of the molded body during the powder supply from the supply hopper and the powder supply from the coater, and the formation of the powder layer on the molding table. In the powder bed fusion method, the powder needs to be evenly spread on the molding table with a certain thickness. The process of spreading the powder is called brushing, and the quality of the powder spreading is called brushing property. The powder used in the layered molding method needs to have sufficient brushing property, so the powder needs to have appropriate fluidity.

[0042] As an index for measuring the fluidity of metal powder, the fluidity (FR: Flow Rate) specified in JIS Z 2502 "Metal Powder - Fluidity Measurement Method" in accordance with ISO 4490 can be used. However, in the case of fine powders with a 50% particle size of 50 μm or less, which is mainly used for the laser powder bed fusion method, the powder sometimes does not flow out of the measurement container and cannot be measured, and the fluidity cannot be evaluated. Therefore, as an index for evaluating the fluidity of fine powders, it is effective to use the adhesion of powders obtained by the direct shear test method for powders (hereinafter referred to as shear test) specified in the "Direct Shear Test Method for Powders" of the Japan Powder Industry Technology Association Standard (SAP15-13: 2013). As for the adhesion, in the shear test, the shear stress generated when a powder layer formed by compacting in the vertical direction is pressed in the vertical direction and is caused to slide laterally in the horizontal direction is measured, and the yield locus of the obtained powder layer can be obtained.

[0043] In the shear test, it can be measured by using, for example, a powder rheometer FT4 manufactured by Freeman Technology. For the copper alloy powder for stacking, if its adhesion is below 0.600 kPa, it can be judged to have sufficient fluidity to cover a uniform powder layer and good brushability. Thus, a high-density and homogeneous stacked body can be obtained. When the adhesion is greater than 0.600 kPa, the fluidity of the copper alloy powder for stacking is insufficient, and the brushability becomes poor and an appropriate powder layer cannot be formed. Therefore, in the copper alloy powder for stacking, it is expected that the adhesion of the copper alloy powder obtained by the yield trajectory obtained by the shear test is below 0.600 kPa.

[0044] <Manufacturing of a Copper Alloy Laminated Formed Body Using the Copper Alloy Powder for Laminated Forming of the Present Embodiment>

[0045] As a method for manufacturing a copper alloy laminated body, various known metal laminated forming technologies can be used. For example, in the powder bed fusion method, the laminated body is produced while repeatedly performing the following steps: using a scraper or roller to flatten and spread the metal powder on the forming table to form a powder layer, irradiating a laser or electron beam to a predetermined position of the formed powder layer to sinter and melt the metal powder. In the forming process of metal laminated forming, in order to obtain a high-quality body, it is necessary to control a lot of process parameters.

[0046] In the laser powder bed fusion method, there are many scanning conditions such as laser output power and laser scanning speed. Therefore, when setting the optimal scanning conditions, the energy density, which is an index summarizing the main parameters, is used to adjust the main parameters. If the laser output power is set to P (W), the laser scanning speed is set to v (mm / s), the laser scanning interval is set to s (mm), and the thickness of the powder layer is set to t (mm), then the energy density E (J / mm 3 ) is determined by E = P / (v×s×t). In the laser powder bed fusion method, the energy density is preferably 150 J / mm 3 Above 450J / mm 3 Below. When the energy density is less than 150J / mm 3 In the case of high energy density, defects such as unmelted powder layer, poor fusion and voids in the molded body may occur. 3 In this case, sputtering occurs and the surface of the powder layer becomes unstable, resulting in defects such as voids in the molded body.

[0047] On the other hand, in the electron beam powder bed melting method, when the electron beam is irradiated to the powder layer, if negative charges are accumulated in the powder layer and charged, it will cause a smoke phenomenon in which the powder flies in a mist-like manner, resulting in poor melting. Therefore, in order to prevent charging, a preparatory process is required to preheat the powder layer and temporarily sinter it. However, when the preheating temperature is too high, sintering progresses and causes necking, and it is difficult to remove the residual powder from the inside of the stacked shape after shaping. Therefore, in the copper alloy powder for stacking shaping, the preheating temperature is preferably set to 300°C or more and 800°C or less.

[0048] It should be noted that the metal stacking forming technology based on the powder bed fusion method is exemplified here, but the general stacking forming method for manufacturing stacked bodies using the copper alloy powder for stacking forming of this embodiment is not limited to this. For example, a stacking forming method based on the directional energy deposition method may also be used.

[0049] (Aging treatment of copper alloy laminated shapes)

[0050] By subjecting the copper alloy laminated body to aging treatment, supersaturated solid solution of nickel and silicon is precipitated, the strength of the laminated body is improved, and the electrical conductivity is improved. Therefore, the aging treatment step is a necessary step to obtain the high strength and high electrical conductivity characteristics of the present embodiment. The aging treatment can be performed by heating the laminated body to a predetermined temperature and maintaining it for a predetermined time. The aging treatment is preferably performed in a reducing atmosphere or in an inert gas in a vacuum.

[0051] The effect of aging treatment is determined by the combination of aging treatment temperature and aging treatment time. Therefore, in terms of the balance between the target characteristics and efficiency, it is important to set appropriate conditions. The aging treatment temperature is preferably 450°C to 550°C. More preferably, it is 450°C to 500°C. In the case where the mechanical strength is particularly improved, it is preferably set to 500°C. In the case where a particularly high electrical conductivity is desired, it can also be set to 550°C or more. When the aging treatment temperature is 450°C or more, the aging treatment time is preferably set to 0.5 hours to 3 hours.

[0052] When the aging treatment time is less than the set time, the precipitation of nickel and silicon becomes insufficient. In addition, when the aging treatment time exceeds the set time, it becomes over-aging, and the precipitated nickel-silicon intermetallic compound coarsens, resulting in a decrease in hardness. When the aging treatment temperature is less than 450°C, it takes a long time to obtain the aging effect, so it is not practical. In addition, when the aging treatment temperature exceeds 550°C, it becomes over-aging, the precipitation phase of the nickel-silicon intermetallic compound coarsens and the strength decreases.

[0053] In the copper alloy laminated body obtained by laminated molding using the copper alloy powder for laminated molding of the present embodiment, the nickel-silicon intermetallic compound becomes easy to precipitate due to the thermal strain introduced by the rapid melting and solidification process which is a characteristic of the laminated molding method. Therefore, even if the aging treatment temperature is 450°C to 550°C and the aging treatment time is about 1 hour, the electrical conductivity and mechanical strength can be sufficiently improved.

[0054] The Vickers hardness of the copper alloy laminated body of the present embodiment is measured by a method in accordance with JIS Z2244: Vickers hardness test - test method. The Vickers hardness can be measured, for example, by a micro hardness tester HMV-G21-DT manufactured by Shimadzu Corporation.

[0055] In addition, the copper alloy laminated body of the present embodiment has an electrical conductivity of 30% IACS or more. The electrical conductivity can be measured by, for example, an eddy current conductivity meter. As an eddy current conductivity meter, for example, a high-performance eddy current conductivity meter SigmaCheck manufactured by Nihon Matech Corporation can be cited. It should be noted that IACS (International Annealed Copper Standard) means: as a benchmark for electrical conductivity, the annealed standard soft copper (volume resistivity: 1.7241×10 -2 The conductivity of the steel sheet (μΩm) is defined as 100% IACS. The conductivity can be adjusted by aging treatment, preferably appropriately adjusted in accordance with the balance between the desired Vickers hardness. The conductivity is preferably 35% IACS or more, more preferably 40% IACS or more.

[0056] It should be noted that in metals, it is known that electrical conductivity and thermal conductivity are in a roughly proportional relationship as per the Wiedemann-Franz theorem. Therefore, the copper alloy laminated body obtained by performing laminated molding using the copper alloy powder for laminated molding of the present embodiment and the laminated molding apparatus has high electrical conductivity and can therefore also be used as a copper alloy laminated body having high thermal conductivity.

[0057] [Second embodiment]

[0058] In this embodiment, a copper alloy powder for stacking molding containing nickel and silicon, and other metal elements, for example, one or more selected from iron, silver, magnesium, manganese, tin and zinc, with the remainder consisting of copper and unavoidable impurities, and a copper alloy stacked body obtained by stacking molding using the copper alloy powder for stacking molding are described.

[0059] The copper alloy powder for laminated molding of the present embodiment may contain one or more elements selected from iron, silver, magnesium, manganese, tin and zinc in addition to nickel and silicon as required. The effects of containing these metal elements will be described below.

[0060] The inclusion of iron has the effect of miniaturizing the microstructure of the copper alloy laminated body of the present embodiment and improving the strength. In addition, iron forms an iron-silicon compound by combining with silicon. Therefore, it is possible to improve mechanical properties and heat resistance without significantly reducing the electrical conductivity. The iron content is preferably adjusted to a range of 0.01% by weight to 1.00% by weight, and more preferably adjusted to a range of 0.05% by weight to 0.30% by weight.

[0061] The inclusion of silver is believed to have the effect of improving the electrical conductivity of the copper alloy laminated body of the present embodiment, and the effect of improving the strength by solid solution strengthening. In addition, it has the effect of increasing the chemical potential of nickel, increasing the mutual repulsion (repulsive interaction) between elements, and thus promoting the precipitation of nickel-silicon intermetallic compounds. When the silver content is greater than 1.0 wt%, the silver ratio is increased, but even if silver is increased, no significant effect can be obtained in terms of characteristics, and the cost is increased due to the excessive inclusion of expensive silver. Therefore, silver is preferably adjusted to a range of 0.01 wt% to 1.00 wt%, and more preferably adjusted to a range of 0.05 wt% to 0.30 wt%.

[0062] The inclusion of magnesium has the effect of improving strength by solid solution strengthening and has the effect of improving stress relaxation resistance. In addition, even if magnesium is contained in the copper alloy, the influence on the electrical conductivity is small. In addition, it has the effect of promoting the precipitation of nickel-silicon intermetallic compounds. Magnesium is preferably adjusted to a range of 0.01 weight % to 1.00 weight %, and more preferably adjusted to a range of 0.05 weight % to 0.35 weight %.

[0063] Manganese can act as a deoxidizer, and can suppress the influence of oxygen by combining with oxygen that degrades the quality to form a compound. In addition, it has the effect of miniaturizing the microstructure and improving the strength. Manganese is preferably adjusted to a range of 0.01% by weight to 1.00% by weight, and more preferably adjusted to a range of 0.05% by weight to 0.20% by weight.

[0064] The inclusion of tin and zinc has the effect of improving strength by solid solution strengthening. In addition, it has the effect of improving stress relaxation resistance, heat resistance, and corrosion resistance. However, if tin and zinc are contained excessively, the conductivity decreases. Therefore, tin is preferably adjusted to a range of 0.01% by weight to 1.00% by weight, and more preferably adjusted to a range of 0.05% by weight to 0.50% by weight. Zinc is preferably adjusted to a range of 0.01% by weight to 1.00% by weight, and more preferably adjusted to a range of 0.05% by weight to 0.50% by weight.

[0065] It should be noted that when the content of iron, silver, magnesium, manganese, tin and zinc exceeds 1.0 wt %, the electrical conductivity is greatly reduced. Therefore, the content of these elements is preferably 1.0 wt % or less in total.

[0066] [Third Embodiment]

[0067] In this embodiment, a comparison result of the characteristics of a copper alloy laminated formed body formed by laminated forming and a copper alloy laminated formed body produced by conventional arc melting or rolling will be described.

[0068] It is known that Corson alloy is subjected to plastic working such as rolling or forging, i.e., severe plastic deformation, to impart strain after solution treatment, and heat treatment to precipitate fine nickel-silicon intermetallic compounds, thereby obtaining excellent properties such as high strength, high electrical conductivity, and high thermal conductivity.

[0069] As a method for manufacturing these Corson alloys, for example, a method is known in which a cast Corson alloy ingot is hot forged, then subjected to solution heat treatment, and then subjected to aging treatment. In addition, a method is known in which a cast Corson alloy ingot is subjected to blanking and hot finishing by forging or rolling, and then subjected to rapid cooling after solution treatment, and then subjected to mechanical processing and aging treatment. In addition, a method is known in which a cast Corson alloy ingot is subjected to hot working, then annealed, and then subjected to aging treatment after cooling. In addition, a method is known in which a cast Corson alloy ingot is hot forged, subjected to cold plastic working after solution treatment, and then subjected to aging treatment.

[0070] However, since Corson alloy ingots are cast, plastic working (forging or rolling) and solution treatment are performed, and aging treatment is performed after these processes, there are the following problems: the processed shape is limited; and since plastic working (forging or rolling) and solution treatment are necessary in the process, there are many processing processes.

[0071] As described above, according to the present embodiment, a high-strength copper alloy laminated body can be manufactured by efficiently generating a Corson alloy containing nickel and silicon.

[0072] Furthermore, according to the present embodiment, by further including iron, silver, magnesium, manganese, tin, and zinc as other metal elements in nickel and silicon, a copper alloy laminated body having further improved electrical conductivity and strength can be manufactured.

[0073] In addition, according to the present embodiment, it is possible to provide copper alloy powder for stacking molding for manufacturing copper alloy stacking bodies that simultaneously achieve high electrical conductivity, high thermal conductivity and excellent mechanical strength, and copper alloy stacking bodies obtained by stacking molding without the need for solution treatment and plastic processing.

[0074] In addition, by using the copper alloy powder for stacking molding of the present embodiment, high electrical conductivity, high thermal conductivity and high strength can be achieved simultaneously, and copper alloy molds for die casting and plastic molding or electrodes for resistance welding can be efficiently manufactured without implementing solution treatment and plastic processing processes.

[0075] [Other embodiments]

[0076] The present invention has been described above with reference to the embodiments, but the present invention is not limited to the above-mentioned embodiments. Various changes that can be understood by those skilled in the art can be made to the composition and details of the present invention within the technical scope of the present invention. In addition, the technology of arbitrarily combining the respective features included in each embodiment is also included in the technical scope of the present invention.

[0077] Example

[0078] Hereinafter, the features of the copper alloy powder for laminated molding and the copper alloy laminated molding shown in this embodiment will be described based on the examples and comparative examples as the experimental results according to this embodiment. The following examples and comparative examples are only specific examples for making the technical content easy to understand, and the technical scope is not limited to these specific examples.

[0079] <Example of Copper Alloy Powder for Laminated Forming Containing Nickel and Silicon>

[0080] Copper alloy powder for laminated molding containing nickel and silicon was produced by changing the content and content ratio of nickel and silicon, and then copper alloy laminated bodies were produced by laminated molding using the copper alloy powder for laminated molding, and their properties were measured.

[0081] (Manufacturing and property measurement of copper alloy powder for laminated molding)

[0082] The copper alloy powder for laminated molding containing nickel and silicon shown in Table 1 was manufactured by gas atomization. Then, the obtained copper alloy powder for laminated molding was classified so that the particle size was 10 μm or more and 45 μm or less for the laser powder bed fusion method, and 45 μm or more and 105 μm or less for the electron beam powder bed fusion method.

[0083] The contents of the component elements in the obtained copper alloy powder for laminated molding were measured by ICP emission spectrometry. In addition, the apparent density (AD) (g / cm 3 ) was measured. In addition, the fluidity (FR) (seconds / 50 g) of the obtained copper alloy powder for laminated molding was measured in accordance with JIS Z 2502. In addition, the 50% particle size (D50) (μm) was measured by laser diffraction method (Microtrac MT3300: manufactured by Microtrac BEL Co., Ltd.).

[0084] A shear test was carried out using a powder rheometer FT4 (manufactured by Freeman Technology) to measure the adhesion (kPa) of the obtained copper alloy powder for stacking molding. The powder for the molding test is actually spread on the molding table of the 3D stacking molding machine (powder sintering stacking molding / laser method or electron beam method) to form a powder layer, thereby evaluating the brushability of the obtained copper alloy powder for stacking molding. The measurement results of the various properties of the copper alloy powder for stacking molding of Examples 1 to 6 and Comparative Examples 1 to 12 are shown in Table 1. In Table 1, the values ​​of the underlined properties indicate values ​​that do not meet the conditional range (expected value) of the copper alloy powder for stacking molding.

[0085] [Table 1]

[0086]

[0087] (Determination of the coating properties of copper alloy powder for laminated molding)

[0088] In Examples 1 to 6 and Comparative Examples 5 to 12, the coating properties were sufficient and the copper alloy laminated bodies could be produced satisfactorily.

[0089] On the other hand, the copper alloy powders of Comparative Examples 1 to 4 had poor coating properties and therefore could not be subjected to normal lamination molding. For example, in the copper alloy powder of Comparative Example 1, the powder was not evenly spread and molding could not be performed. The copper alloy powder of Comparative Example 1 satisfied the conditions for the content and ratio of nickel and silicon and the 50% particle size (D50), but did not satisfy the conditions for the apparent density (AD) and adhesion.

[0090] The copper alloy powder of Comparative Example 2 cannot form a powder layer. For the copper alloy powder of Comparative Example 2, the content and ratio of nickel and silicon meet the conditions, but the 50% particle size (D50), apparent density (AD) and adhesion do not meet the conditions. The copper alloy powder of Comparative Example 3 can be spread fully, but there are many sparse parts in the powder layer. For the copper alloy powder of Comparative Example 3, the content and ratio of nickel and silicon, 50% particle size (D50) and apparent density (AD) meet the conditions, but the adhesion does not meet the conditions. In the copper alloy powder of Comparative Example 4, the powder layer is not filled sufficiently and the density is low. For the copper alloy powder of Comparative Example 4, the content and ratio of nickel and silicon, 50% particle size (D50) and adhesion meet the conditions, but the apparent density (AD) does not meet the conditions.

[0091] (Manufacturing of Copper Alloy Laminated Forming Body Using Copper Alloy Powder for Laminated Forming)

[0092] The copper alloy powder for stacking molding of Examples 1 to 5 and Comparative Examples 5 to 12 was used to manufacture the stacked molding body for the test using a 3D powder stacking molding machine (SLM Solutions GmbH, SLM280HL) equipped with a Yb fiber laser with a wavelength of 1064 nm. The stacking molding was performed at a stacking thickness of 25 μm to 50 μm, a laser output power of 300 W to 700 W, a scanning speed of 900 mm / s to 1500 mm / s, and an energy density of 150 J / mm 3 Above 450J / mm 3 The following conditions were used.

[0093] The copper alloy powder for lamination molding in Example 6 was used to manufacture a lamination molding body for testing using a 3D powder lamination molding machine (Arcam AB, EBM A2X) equipped with an electron beam. The lamination molding was performed under the conditions of a lamination thickness of 50 μm to 100 μm, an electron beam voltage of 60 kV, and a preheating temperature of 300°C to 700°C. In the lamination molding, a 3D powder lamination molding machine was used to manufacture A cylindrical stacked shape with a height of 10 mm.

[0094] (Determination of properties of copper alloy laminated bodies)

[0095] The relative density (%) of the laminated bodies produced using the copper alloy powders for laminated molding of Examples 1 to 6 and Comparative Examples 5 to 12 was measured by the Archimedean method using helium as a substitution medium (AccuPyc1330: manufactured by Shimadzu Corporation).

[0096] For the copper alloy laminated bodies of Examples 1 to 6 and Comparative Examples 5 to 12 manufactured using a 3D powder laminated molding machine, the electrical conductivity (% IACS) was measured using an eddy current conductivity meter (high performance eddy current conductivity meter SigmaCheck: manufactured by Nihon Matech Corporation). In addition, the Vickers hardness (Hv) of the copper alloy laminated bodies was measured using a micro hardness tester (micro hardness tester HMV-G21-DT: manufactured by Shimadzu Corporation).

[0097] In an inert atmosphere, the temperature was set to 400°C, 500°C, 600°C and 700°C, and the produced copper alloy stacked body was subjected to an aging treatment for 1 hour. The conductivity of the copper alloy stacked body subjected to the aging treatment was measured using an eddy current conductivity meter. In addition, the Vickers hardness was measured using a micro hardness tester. For the stacked bodies of Examples 1 to 6 and Comparative Examples 5 to 12 manufactured using a 3D powder stacking molding machine, the evaluation results of various properties are shown in Table 2. In Table 2, the values ​​of the properties surrounded by a thick frame represent values ​​that satisfy the condition range as a copper alloy stacked body. In addition, the values ​​of the underlined properties represent values ​​that do not satisfy the condition range as a copper alloy stacked body even under an aging treatment at 500°C, and values ​​that do not satisfy the condition range as a copper alloy powder for stacking molding.

[0098] [Table 2]

[0099]

[0100] In Examples 1 to 6, the contents and ratios of nickel and silicon, as well as the properties of the copper alloy powder used for stacked molding are within the conditions, so that through the prescribed aging treatment, a copper alloy stacked body having sufficient electrical conductivity (above 30% IACS) and strength (Vickers hardness: above 200 Hv) can be formed.

[0101] On the other hand, in Comparative Example 5, the nickel and silicon contents were excessive and outside the condition range, so the electrical conductivity was low despite the high Vickers hardness. In Comparative Example 6, the nickel and silicon contents were too low and outside the condition range, so the electrical conductivity was high but the Vickers hardness was low. In Comparative Example 7, the nickel content was excessive, and in Comparative Example 9, the silicon content was excessive, so the electrical conductivity was low despite the high Vickers hardness. In Comparative Example 8, the nickel content was too low, and in Comparative Example 10, the silicon content was too low, so the electrical conductivity was high but the Vickers hardness was low.

[0102] The value (ratio) obtained by dividing the nickel content (weight %) by the silicon content (weight %) was higher than 7.2 in Comparative Example 11 and lower than 3.3 in Comparative Example 12. Therefore, although the Vickers hardness was high, the electrical conductivity was low.

[0103] Figure 1 In Examples 1 to 6 and Comparative Examples 5 to 12, the electrical conductivity (% IACS) after aging treatment at 500° C. is plotted on the X-axis and the Vickers hardness (Hv) is plotted on the Y-axis.

[0104] It is shown that the electrical conductivity and Vickers hardness of the copper alloy laminated structures of Examples 1 to 6 satisfy the conditional range, while the electrical conductivity and Vickers hardness of the copper alloy laminated structures of Comparative Examples 5 to 12 do not satisfy the conditional range.

[0105] in addition, Figure 2 This is a graph plotting the characteristics of electrical conductivity (%IACS) or Vickers hardness (Hv) when the aging treatment temperature was changed from 400°C to 700°C in Examples 1 to 6.

[0106] It is understood that the temperature range of the aging treatment in Examples 1 to 6 is preferably 450°C or higher and 550°C or lower. When the electrical conductivity is to be improved, 550°C is preferred, and when the Vickers hardness is to be improved, 500°C is preferred.

[0107] <Example of Copper Alloy Powder for Laminated Forming Containing Nickel, Silicon, and Other Metal Elements>

[0108] The contents and ratios of nickel and silicon and the contents of other metal elements were varied to produce copper alloy powder for laminated molding, and then copper alloy laminated bodies were produced by laminated molding using the copper alloy powder for laminated molding, and their properties were measured.

[0109] (Manufacturing and property measurement of copper alloy powder for laminated molding)

[0110] Copper alloy powder for laminated molding containing nickel and silicon and other metal elements shown in Table 3 was manufactured by gas atomization. Then, the obtained copper alloy powder for laminated molding was classified so that the particle size was 10 μm or more and 45 μm or less for laser powder bed fusion method, and 45 μm or more and 105 μm or less for electron beam powder bed fusion method.

[0111] The contents of the component elements in the obtained copper alloy powder for laminated molding were measured by ICP emission spectrometry. In addition, the apparent density (AD) (g / cm 3) was measured. In addition, the fluidity (FR) (seconds / 50 g) of the obtained copper alloy powder for laminated molding was measured in accordance with JIS Z 2502. In addition, the 50% particle size (D50) (μm) was measured by laser diffraction method (Microtrac MT3300: manufactured by Microtrac BEL Co., Ltd.).

[0112] The shear test was carried out using a powder rheometer FT4 (manufactured by Freeman Technology) to measure the adhesion (kPa) of the obtained copper alloy powder for stacking. The powder for the forming test was actually spread on the forming table of the 3D stacking forming machine (powder sintering stacking forming / laser method or electron beam method) to form a powder layer, thereby evaluating the brushability of the obtained copper alloy powder for stacking forming. The measurement results of various properties of the copper alloy powder for stacking forming of Examples 10 to 19 are shown in Table 3.

[0113] [Table 3]

[0114]

[0115] (Manufacturing of Copper Alloy Laminated Forming Body Using Copper Alloy Powder for Laminated Forming)

[0116] The copper alloy powders for layered molding of Examples 10 to 13 and 15 to 19 were used to produce layered moldings for testing using a 3D powder layered molding machine (SLM Solutions GmbH, SLM280HL) equipped with a Yb fiber laser of a wavelength of 1064 nm. The layered molding was performed at a layer thickness of 25 μm to 50 μm, a laser output power of 300 W to 700 W, a scanning speed of 900 mm / s to 1500 mm / s, and an energy density of 150 J / mm 3 Above 450J / mm 3 The following conditions were used.

[0117] The copper alloy powder for lamination molding in Example 14 was used to manufacture a lamination molding body for testing using a 3D powder lamination molding machine (Arcam AB, EBM A2X) equipped with an electron beam. The lamination molding was performed under the conditions of a lamination thickness of 50 μm to 100 μm, an electron beam voltage of 60 kV, and a preheating temperature of 300°C to 700°C. In the lamination molding, a 3D powder lamination molding machine was used to manufacture A cylindrical stacked shape with a height of 10 mm.

[0118] (Determination of properties of copper alloy laminated bodies)

[0119] The relative density (%) of the laminated bodies produced using the copper alloy powders for laminated formation of Examples 10 to 19 was measured by the Archimedean method using helium as a substitution medium (AccuPyc1330: manufactured by Shimadzu Corporation).

[0120] For the copper alloy laminated bodies of Examples 10 to 19 manufactured using a 3D powder laminated forming machine, the electrical conductivity (% IACS) was measured using an eddy current conductivity meter (high performance eddy current conductivity meter SigmaCheck: manufactured by Nihon Matech Corporation). In addition, the Vickers hardness (Hv) of the copper alloy laminated bodies was measured using a micro hardness tester (micro hardness tester HMV-G21-DT: manufactured by Shimadzu Corporation).

[0121] In an inert atmosphere, the temperature was set to 400°C, 500°C, 600°C and 700°C, and the copper alloy laminated body was subjected to aging treatment for 1 hour. The conductivity of the copper alloy laminated body subjected to aging treatment was measured using an eddy current conductivity meter. In addition, the Vickers hardness was measured using a micro hardness tester. For the laminated bodies of Examples 10 to 19 manufactured using a 3D powder laminated forming machine, the evaluation results of various properties are shown in Table 4. In Table 4, the values ​​of the properties surrounded by the thick frame represent values ​​that meet the condition range for the copper alloy laminated body.

[0122] [Table 4]

[0123]

[0124] In Examples 10 to 19, the contents and ratios of nickel and silicon, as well as the properties of the copper alloy powder used for stacked molding are within the conditions, so that through the prescribed aging treatment, a copper alloy stacked body having sufficient electrical conductivity (above 30% IACS) and strength (Vickers hardness: above 200 Hv) can be formed.

[0125] Figure 3 In Examples 10 to 19, the electrical conductivity (% IACS) after aging treatment at 500° C. is plotted on the X-axis and the Vickers hardness (Hv) is plotted on the Y-axis.

[0126] It is shown that the electrical conductivity and Vickers hardness of the copper alloy laminated bodies of Examples 10 to 19 satisfy the conditional range.

[0127] In addition, as for Examples 10 and 11, which are copper alloy stacked structures containing nickel, silicon and iron, the decrease in electrical conductivity is suppressed, and the Vickers hardness is greatly improved regardless of the aging treatment temperature, compared with Example 1, which is a copper alloy stacked structure containing the same amount of nickel and silicon and no iron.

[0128] In Example 15, which is a copper alloy laminated structure containing nickel, silicon and silver, the Vickers hardness is substantially the same as that of Example 1, which is a copper alloy laminated structure containing the same nickel and silicon and not containing silver, and the electrical conductivity is improved. In Example 16, the electrical conductivity is maintained at the same value and the Vickers hardness is improved.

[0129] In Example 17, which is a copper alloy laminated structure containing nickel, silicon and magnesium, the decrease in electrical conductivity is suppressed and the Vickers hardness is improved compared with Example 2, which is a copper alloy laminated structure containing equivalent nickel and silicon and no magnesium.

[0130] In Example 18, which is a copper alloy stacked structure containing nickel, silicon, magnesium and manganese, the Vickers hardness after aging treatment at 500°C is significantly improved compared to Example 1, which is a copper alloy stacked structure containing equivalent nickel and silicon and neither magnesium nor manganese.

[0131] In Example 19, which is a copper alloy stacked structure containing nickel, silicon, tin and zinc, the Vickers hardness is improved regardless of the heat treatment conditions, compared with Example 3, which is a copper alloy stacked structure containing the same amount of nickel and silicon and neither tin nor zinc.

[0132] in addition, Figure 4 This is a graph plotting the characteristics of electrical conductivity (%IACS) or Vickers hardness (Hv) when the aging treatment temperature was changed from 400°C to 700°C in Examples 10 to 19.

[0133] It is understood that the temperature range of the aging treatment in Examples 10 to 19 is preferably 450°C or higher and 550°C or lower. When the electrical conductivity is to be improved, 550°C is preferred, and when the Vickers hardness is to be improved, 500°C is preferred.

[0134] <Comparative Example of Copper Alloy Shaped Body Containing Nickel and Silicon by Arc Melting or Rolling>

[0135] (Arc Melting Materials)

[0136] In order to compare the properties of the copper alloy (Corson alloy) produced by the conventional production method of subjecting the cast Corson alloy ingot to plastic working and solution treatment with the properties of the copper alloy laminated bodies of Examples 1 to 6 and 10 to 19, the properties of the Corson alloy produced by the conventional method were evaluated using the following method. As an alternative to the casting material production method, an arc melting method, which is a known method for producing molten material, was used.

[0137] Arc-melted materials were prepared by arc melting the same copper alloy powder for stacking molding as in Examples 1 to 5, 10 to 13, and 15 to 19. The arc-melted materials were prepared as follows. First, the copper alloy powder for stacking molding of Examples 1 to 5, 10 to 13, and 15 to 19 was press-molded to prepare a powder compact. The prepared powder compact was arc-melted in an argon atmosphere using a vacuum arc melting furnace manufactured by Nissin Giken Co., Ltd. to prepare an arc-melted material. The arc-melted materials were used as Comparative Examples 21 to 34. It should be noted that Example 6 had the same composition as Example 1, and Example 14 had the same composition as Example 10, so arc-melted materials using the same copper alloy powder for stacking molding as in Examples 6 and 14 were not prepared.

[0138] The arc-melted materials of Comparative Examples 21 to 34 produced by arc melting were measured for conductivity (% IACS) using an eddy current conductivity meter (high performance eddy current conductivity meter SigmaCheck: manufactured by Nihon Matech Corporation). In addition, the Vickers hardness (Hv) was measured using a micro-hardness tester (micro-hardness tester HMV-G21-DT: manufactured by Shimadzu Corporation).

[0139] In addition, the arc-melted materials were subjected to aging treatment for 1 hour at a temperature of 400, 500, 600, and 700° C. in an inert atmosphere. The electrical conductivity of the arc-melted materials subjected to aging treatment was measured using an eddy current conductivity meter. In addition, the Vickers hardness was measured using a microhardness tester.

[0140] The evaluation results of various properties of the arc-melted materials of Comparative Examples 21 to 34 are shown in Table 5. In Table 5, the underlined values ​​of the properties indicate values ​​that do not satisfy the condition range for the copper alloy molding even in the aging treatment at 500°C.

[0141] [Table 5]

[0142]

[0143] (Arc-melted material after rolling)

[0144] Next, the arc-melted materials of Comparative Examples 21 to 34 were rolled at a processing rate of 50% using a rolling machine to perform plastic working. The rolled bodies were subjected to a solution treatment for 1 hour at a temperature of 950° C. in an inert atmosphere. The arc-melted materials subjected to this rolling processing were designated as Comparative Examples 41 to 54.

[0145] For Comparative Examples 41 to 54, which were arc-melted materials obtained by rolling the arc-melted materials of Comparative Examples 21 to 34, the electrical conductivity (%IACS) was measured using an eddy current conductivity meter (high-performance eddy current conductivity meter SigmaCheck: manufactured by Nihon Matech Corporation). In addition, the Vickers hardness (Hv) was measured using a micro-hardness tester (micro-hardness tester HMV-G21-DT: manufactured by Shimadzu Corporation).

[0146] The arc-melted material subjected to rolling was subjected to aging treatment for 1 hour at a temperature of 400, 500, 600, and 700°C in an inert atmosphere. The electrical conductivity of the arc-melted material subjected to aging treatment and rolling was measured using an eddy current conductivity meter. In addition, the Vickers hardness was measured using a microhardness tester.

[0147] The evaluation results of various properties of the arc-melted materials subjected to rolling of Comparative Examples 41 to 54 are shown in Table 6. In Table 6, the underlined property values ​​indicate values ​​that do not satisfy the condition range for the copper alloy shape even after aging treatment at 500°C.

[0148] [Table 6]

[0149]

[0150] Figure 5 The graph shows the properties of the copper alloy laminated bodies of Examples 1 to 6 and 10 to 19, and the properties of the arc-melted materials of Comparative Examples 21 to 34 and the arc-melted materials subjected to rolling of Comparative Examples 41 to 54, when aged at 500°C, with the electrical conductivity (%IACS) being plotted on the X-axis and the Vickers hardness (Hv) being plotted on the Y-axis.

[0151] Since the arc-melted materials of Comparative Examples 21 to 34 were not subjected to strong plastic deformation to impart strain after solution treatment, even if heat treatment was performed, the properties were inferior to those of Examples 1 to 6 and 10 to 19. Compared with the properties of the arc-melted materials of Comparative Examples 41 to 54 subjected to rolling processing produced by a conventional manufacturing method, the copper alloy laminated bodies of Examples 1 to 6 and 10 to 19 were able to achieve comparable properties.

[0152] From the above, it was confirmed that Examples 1 to 6 and 10 to 19 can provide copper alloy powder for laminated molding and copper alloy laminated molded bodies that achieve both high electrical conductivity (thermal conductivity) and excellent mechanical strength without requiring solution treatment and plastic working processes.

Claims

1. A copper alloy powder for laminated molding, the copper alloy powder being used for molding a laminated body by a laminated molding method, The copper alloy powder for laminated molding contains nickel and silicon, and the remainder is composed of copper and inevitable impurities. The value obtained by dividing the nickel content (weight %) by the silicon content (weight %) is 3.3 or more and 7.2 or less. 2 . The copper alloy powder for laminated molding according to claim 1 , comprising 1.5 wt % to 6.0 wt % of the nickel. 3 . The copper alloy powder for laminated molding according to claim 2 , comprising 0.35 wt % to 1.5 wt % of the silicon. 4 . The copper alloy powder for laminated molding according to claim 1 , wherein a 50% particle size thereof is 3 μm or more and 200 μm or less.

5. The copper alloy powder for laminated molding according to any one of claims 1 to 3, wherein The apparent density of the powder when measured by the measurement method of JIS Z 2504 (ISO 3923-1) is 3.5 g / cm 3 above.

6. The copper alloy powder for laminated molding according to any one of claims 1 to 3, wherein The adhesion of the copper alloy powder obtained from the yield locus obtained by the shear test was 0.600 kPa or less.

7. The copper alloy powder for laminated molding according to any one of claims 1 to 3, further comprising 1.0 wt% or less in total of one or more selected from iron, silver, magnesium, manganese, tin and zinc (wherein, Excluding the case where iron, silver, magnesium, manganese, tin and zinc are 0% by weight).

8. A copper alloy laminated body obtained by performing laminated molding using the copper alloy powder for laminated molding according to claim 1 and a laminated molding apparatus, The value obtained by dividing the nickel content (weight %) by the silicon content (weight %) is 3.3 or more and 7.2 or less.

9. A copper alloy laminated body obtained by laminating and molding the copper alloy powder for laminating and molding according to claim 3 using a laminating and molding apparatus, The value obtained by dividing the nickel content (weight %) by the silicon content (weight %) is 3.3 or more and 7.2 or less, The copper alloy laminated structure contains 1.5% by weight to 6.0% by weight of the nickel and 0.35% by weight to 1.5% by weight of the silicon, with the remainder being copper and inevitable impurities.

10. The copper alloy laminated body according to claim 8 or 9, which has an electrical conductivity of 30% IACS or more and a Vickers hardness of 200 Hv or more.

11. A copper alloy laminated body obtained by laminating and molding the copper alloy powder for laminating and molding according to claim 7 using a laminating and molding apparatus, The value obtained by dividing the nickel content (weight %) by the silicon content (weight %) is 3.3 or more and 7.2 or less, The copper alloy laminated body contains 1.5 wt% to 6.0 wt% of the nickel, 0.35 wt% to 1.5 wt% of the silicon, and 1.0 wt% to 1.5 wt% of one or more selected from iron, silver, magnesium, manganese, tin and zinc (including 1.0 wt% to 1.0 wt% of one or more selected from iron, silver, magnesium, manganese, tin and zinc in total). Excluding the case where iron, silver, magnesium, manganese, tin and zinc are 0 weight %), the remainder is composed of copper and inevitable impurities.

12. The copper alloy laminated body according to claim 11, having an electrical conductivity of 30% IACS or more and a Vickers hardness of 200 Hv or more.

13. A method for manufacturing a copper alloy laminated body, comprising: Using the copper alloy powder for stacking molding according to any one of claims 1 to 3, stacking molding a copper alloy stacking body using a stacking molding device; and The copper alloy laminated body is maintained at a temperature of 450° C. to 550° C.

Citation Information

Patent Citations

  • Cu-BASED ALLOY POWDER

    JP2021017639A